Editorial (english) - Kahlmeyer-Mertens, Roberto Saraiva; Escudero, Jesús Ádrian (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2020)
Aoristo International Journal of Phenomenology, Hermeneutics and Metaphysics latest issue is its first composed exclusively by articles stemming from a continuous influx of submissions. Among articles, translations and reviews, the current issue brings works on related topics, ratifying the journal vocation of spreading philosophical thinking, allied to its legit aspiration of congregating both domestic and overseas researchers of academic relevance.